Chinese herbal medicine for symptoms of depression and anxiety in chronic obstructive pulmonary disease: A systematic review and meta-analysis. (November 2021) - Yang, Shuang; Xu, Yong; Peng, Wenpan; Han, Di; Feng, Fanchao; Wang, Zhichao; Gu, Cheng; Zhou, Xianmei; He, Hailang
Abstract: Objectives: To evaluate the efficacy and safety of Chinese herbal medicine (CHM) on symptoms of depression and anxiety complicated by chronic obstructive pulmonary disease (COPD). Methods: Literature from 8 electronic medical databases were searched for meta-analysis using RevMan (version 5.3) and Stata (version 12.0) software. The GRADE Pro Guideline Development Tool and TSA Viewer (version.0.9.5.10 beta) were adopted to evaluate the certainty and conclusiveness of the evidence. Results: 26 studies involving 2529 participants were identified. CHM demonstrated significant lower scores on the Hamilton Depression Rating Scale, Self-Rating Depression Scale, Hamilton Anxiety Rating Scale, and Self-Rating Anxiety Scale compared to the control group without CHM. Moreover, CHM showed favorable safety. Conclusions: The evidence verified the efficacy and safety of CHM on relieving depression and anxiety in COPD. However, further large-scale and rigorously designed studies are urgently warranted to strengthen the evidence. Highlights: The efficacy of Chinese herbal medicine (CHM) for depression and anxiety in COPD was systematically evaluated. 26 studies involving 2529 participants were included in the present meta-analysis. CHM was found to be effective in alleviating depression and anxiety accompanied by COPD.